Tatak Pilipino [episode no. 58] [videorecording]. ([Quezon City ABS-CBN], 1992)
A unique display of Pilipino ways and style.
Letras y figuras (5 min.) -- Ben Farrales (5 min.) -- Thomasites educators (5 min.) -- Tatlong bugtong (5 min.) -- Souvenir mentality (10 min.) -- U.F.O. spirituality series-Philippines (15 min.) -- Historical rap calendar events of January (5 min.).
Jim Paredes and Gel Santos Relos.
Keywords: Farrales, Ben; Decoration and ornament; American teachers -- Philippines; Riddles, Philippine; Souvenirs (Keepsakes).; Unidentified flying objects -- Religious aspects; Philippines -- History; Philippine literature; Education; Fine arts; Sociology